Django Framework and Python-Gammu as Middleware SMS Broadcast - Puji Winar Cahyo; Arief Ikhwan Wicaksono (Compiler, 2019)
Because the growing of mobile technology in recently days, technology practitioners are required to be able to create a variety of devices and media that support the mobile technology. Application developers compete to create mobile applications that have a variety of features, including video call, voice sending, image sending or text messaging. Developing of mobile applications have an impact on using of Short Message Service, although using of Short Message Service began to shift, but the Short Message Service feature cannot be abandoned, because Short Message Service is a standard feature carried by mobile devices (mobile phones). For this reason, we need to develop Short Message Service Broadcast middleware as an intermediary for Short Message Service communication between web technology and mobile devices. This technology is using for disseminating information between systems that have been built with mobile devices via Short message service. Broadcast system will produce information about new student admissions, That will be received directly by Senior High School Students through their mobile phones. The Middleware can send message broadcast in real time to more than 500 cellular numbers automatically with an average time of 13 seconds for one message. The advantage of using this technology is direct configuration with Python Back-End. Meanwhile, Technology for message inbox still requires further configuration.